From Separate Formal Specifications to Certified Integrated Visual Modelling Techniques and Environments - Position Statement - Ehrig, Hartmut (Electronic Communications of the EASST, 2010)
In this position statement we discuss the state of the art and role of formal specification and modelling techniques in different periods with special focus on the work of the TFS-group at TU-Berlin. In the past (1970 – 1990) single formal specification techniques have been developed with little impact on practical software development. In the present (1990 – 2010) integrated and visual modelling techniques have gained more and more importance. For the future (2010 – 2020) we try to sketch the idea of a Certified Integrated Visual Modelling Technique and Environment based on an integration of graph theory, graph transformation and Petri net theory, short Dynamic Graph and Net Theory.